Electron beam transport and energy deposition in heterogeneous assemblies of the hastelloy samples embedded into the molten fluorides mix - Bakai, A.S.; Bratchenko, M.I.; Dyuldya, S.V. (Вопросы атомной науки и техники, 2005)
By means of the Monte Carlo computer modeling technique the depth dependencies of energy deposition and concentration of radiation induced point defects have been calculated in heterogeneous assemblies of Hastelloy plates embedded into the melt of fluoride salts and irradiated by 8–10 MeV electron beams. For assemblies of various designs the beam penetration depth dependencies of energy spectra, angular distributions and energy fluxes of electrons and secondary gamma quanta had been studied in great details. As a result of these investigations the optimization of the target assembly design for the imitating experiment at the LUE-10 linac has been accomplished. It has been shown that for the optimized target ampoule design at the experimental conditions (700 hrs long 10 MeV electron irradiation) different surfaces of the Hastelloy plates contacting with molten fluorides are characterized by substantially different values of specific energy deposition (from ~5 keV/atom down to ~60 eV/atom) arising from inelastic ionization energy losses of primary and secondary charged particles. The concentration of point defects produced in elastic collisions of charged particles with target atoms decreases by ~500 times along the assembly thickness. Therefore the single imitating experiment opens up the possibility to study the radiation and corrosion stability of Hastelloy irradiated in the molten fluorides medium in a wide range of doses of electron beam energy deposition and radiation damage of alloy.